2017
DOI: 10.1159/000452652
|View full text |Cite
|
Sign up to set email alerts
|

Airbag-Associated Severe Blunt Eye Injury Causes Choroidal Rupture and Retinal Hemorrhage: A Case Report

Abstract: A case of choroidal rupture caused by airbag-associated blunt eye trauma and complicated with massive subretinal hemorrhage and vitreous hemorrhage that was successfully treated with intravitreal injection of expansile gas and bevacizumab is presented. A 53-year-old man suffered from loss of vision in his right eye due to blunt eye trauma by a safety airbag after a traffic accident. On initial examination, the patient had no light perception in his right eye. Dilated ophthalmoscopy revealed massive subretinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Despite the relatively rare occurrence of vitreoretinal complications with airbag impact, there are a wide variety of clinical presentations of this disorder, such as vitreous hemorrhage, 48 retinal tear, 18 , 20 retinal detachment, 9 choroidal rupture 15 and macular disorders. 21 , 49 Severe blunt trauma has been shown to decrease the anterior-posterior diameter of the globe by 41%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the relatively rare occurrence of vitreoretinal complications with airbag impact, there are a wide variety of clinical presentations of this disorder, such as vitreous hemorrhage, 48 retinal tear, 18 , 20 retinal detachment, 9 choroidal rupture 15 and macular disorders. 21 , 49 Severe blunt trauma has been shown to decrease the anterior-posterior diameter of the globe by 41%.…”
Section: Discussionmentioning
confidence: 99%
“… 30 This result of ocular outer surface strain suggests that the retina or choroid might suffer the greatest damage, resulting in sight-threatening complications reported previously. 9 , 15 , 49 Deformation rate of the vitreous was very low, and the vitreous might act as a shock absorber against the deformation caused by the anterior segment due to its large volume. However, an interesting tendency was that vitreous length showed elongation in the later phase of airbag impact in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An airbag impact can result in severe ocular damage, significant loss of vision, and, in extreme cases, complete loss of the eye [4]. Ocular injuries caused by airbags have been widely reported in the literature [5][6][7][8][9][10][11][12][13][14][15][16], and most injuries require immediate emergency surgery and numerous follow-up surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although airbags significantly suppress passengers' injuries, still in recent years, several cases of variety of eye injuries have been documented due to airbag deployment. [3][4][5][6] In an epidemiological study, Pearlman et al 7 reported that between 1991 and 2000, there were a total of 263 incidents of airbag-related eye injuries in 101 patients that could cause a variety of eye injuries. From an anatomical perspective, the type of eye injury with the highest incidence was corneal injuries, which accounted for 21.6% of all eye injuries.…”
Section: Introductionmentioning
confidence: 99%